2007
DOI: 10.1007/s00066-007-1589-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Painful Heel Spurs

Abstract: RT is an effective treatment option for the management of inflammatory heel spurs. The dose for an RT course should not exceed 3.0 Gy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 34 publications
2
28
0
3
Order By: Relevance
“…However, other studies found no influence of this patient characteristic on treatment outcome [24,30,39].…”
Section: Patients' Agementioning
confidence: 81%
See 4 more Smart Citations
“…However, other studies found no influence of this patient characteristic on treatment outcome [24,30,39].…”
Section: Patients' Agementioning
confidence: 81%
“…To the best of our knowledge, in no study, an influence of gender on treatment outcome has been confirmed [22,24,30,38,39]. In contrast to radiotherapy for oncological indications with high doses, efficacy and tolerability of LD-EBRT seems to be the same concerning gender.…”
Section: Gendermentioning
confidence: 84%
See 3 more Smart Citations